Women in the legal professions: From the eradication of direct discrimination to the prevalence of “epistfemicide” and the glass ceiling - Heim Daniela; Piccone Maria Veronica (Glasnik Etnografskog Instituta SANU, 2022)
The article analyses the situation of women in the legal professions in Argentina, with special reference to the Argentine judicial system. It enquires into the context of the main socio-legal transformations that allowed Argentine women, initially, to access higher education, professional practice and political citizenship and, later, to access the rights that provide the framework to have a life free of gender-based discrimination, including the cluster of LGBTI+ rights. It describes the incorporation of gender mainstreaming into the legal and institutional universe of legal professions in recent decades. Lastly, it reflects on two dimensions of gender-based discrimination that still prevail: that of epistfemicide and that of the glass ceiling, and provides some keys to design strategies for its eradication.